Perception of Noise Pollution in a Youth and Adults School in Curitiba-PR - Borges Filho,Orlando (2017)
Abstract Introduction Nowadays noise remains the third largest cause of environmental pollution on Earth. It appears that despite the existing noise control legislation the issue deserves further supervision by the public authorities so that the ceilings established for the various activities are observed. People exposed to noise are more likely to develop numerous auditory and non-auditory problems directly impacting persona family and working life. Objectives The objective of this study is to research and consequently understand how the population of students of a youth and adult school in Curitiba perceives noise pollution as well as look into the actions that the school adopts in order to guide the students on the topic. Method We applied a structured questionnaire to 120 individuals and assessed the following variables: characterization of the place of residence occupation leisure health and perception of soundscapes. We also applied a closed questionnaire about educational actions for noise pollution to the school’s geography teacher. Results Questionnaire responses show that people perceive noise in the most diverse environments they frequent and are able to identify the source of the noise but this perception proved fragile as themajority does not takemeasures to prevent ormitigate these noises. At school there are no actions aimed at environmental education on the subject studied. Conclusion The studied group does not perceive the noise as a harmful agent and does not prevent themselves from it and the school not work contents related to noise pollution leaving a significant gap in the awareness process of this population.